The number of retrieved lymph nodes needed for accurate staging differs based on the presence of preoperative chemoradiation for rectal cancer - Han, Jeonghee (Medicine (Baltimore), 2016)
The aim of this study is to investigate if retrieval of 12 lymph nodes (LNs) is sufficient to avoid stage migration as well as to evaluate the prognostic impact of insufficient LN retrieval in different treatment settings of rectal cancer, particularly in the case of preoperative chemoradiotherapy (pCRT). The data of all patients with biopsy proven rectal adenocarcinoma who underwent curative surgery between January 2005 and December 2012 were analyzed. Univariate and multivariate analyses for oncologic outcomes were performed in LN metastasis or no LN metastasis (LN−) group. Subgroup analyses were performed according to whether a patient had received pCRT. A total of 1825 patients were enrolled into the study. The maximal Chi-square method revealed the minimum number of harvested LNs required to be 12. Univariate and multivariate analyses found LNs ≥ 12 to be an independent prognostic factor for both overall survival (OS) (hazard ratio [HR] = 0.5, 95% confidence intervals [CIs]: 0.3–0.8; P = 0.002) and disease-free survival (DFS) (HR = 0.6, 95% CI: 0.4–0.7; P < 0.001) in the LN− group. In the LN− group, LNs ≥ 12 continued to be a significant prognostic factor both for OS and DFS in the subgroup of patients who did not undergo pCRT. However, in the subgroup of the LN− patients who underwent pCRT, LN ≥ 8 was significant for DFS and OS. Retrieval of LNs ≥ 12 and LNs ≥ 8 should be achieved to obtain accurate staging and optimal treatment for the non-pCRT and pCRT groups in rectal cancer, respectively.